MANAJEMEN PONDOK PESANTREN SEBAGAI PILAR PENDIDIKAN ISLAM BERKELANJUTAN - Wahyudi, Wahyudi (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
Pondok pesantren plays a strategic role as a sustainable pillar of Islamic education in Indonesia. It is not merely an educational institution but also a center for moral and spiritual development, Islamic propagation (dakwah), and community empowerment. However, pesantren face various challenges, including resource limitations, technological integration, curriculum standardization, and competition with formal educational institutions. The rapid changes brought by modernization and globalization demand adaptive and innovative management approaches. This study explores strategies for overcoming these challenges through curriculum reform, teacher training, financial transparency, and technology integration. Strengthening community relations and fostering partnerships with government and private institutions are also essential for pesantren sustainability. In conclusion, effective management enables pesantren to remain a key pillar of Islamic education, producing morally upright and competitive generations while preserving its traditional values and responding to contemporary demands.